Teachers' Strategies in Pancasila Education to Cultivate Critical Thinking Skills among Vocational High School Students in The AI-Driven World - Sari, Elly Sukma; Patmisari, P (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to explain how Pancasila Education teachers develop students' critical thinking skills at SMK Negeri 2 Surakarta in facing an AI-driven world, focusing on strategies for designing, implementing, and evaluating Problem-Based Learning and group discussions to foster logical, analytical, and reflective thinking without reliance on AI.Methodology: This research employs a descriptive qualitative approach with a case study design. The participants include the Curriculum Team, Pancasila Education teachers, and students from Construction and Housing Engineering, Geomatics Engineering, Electronics Engineering, Building Modeling and Information Design, and Metal Welding and Fabrication programs. Data were collected through classroom observations, in-depth interviews, and document analysis of lesson plans, teaching materials, and assessment instruments. Data were analyzed using an interactive model involving data reduction, data display, and conclusion drawing, with validity ensured through triangulation and member checking.Results: Research shows that implementing Problem-Based Learning and group discussions is efficacious in improving students' critical thinking skills. Teachers act as facilitators who encourage students to analyze information, evaluate various perspectives, and draw rational conclusions. The use of AI is employed as a tool to assist in information searching, but it is limited to prevent dependency and to continue stimulating students' independent thinking processes.Applications/Originality/Value: This study highlights the strategic role of Pancasila Education teachers in strengthening students' critical thinking in an AI-driven world. The integration of active learning strategies with controlled AI use helps prevent technological dependence and prepares students to make rational decisions in an AI-based workforce.